2012
DOI: 10.1136/bmjopen-2012-000847
|View full text |Cite
|
Sign up to set email alerts
|

Unsatisfactory rates vary between cervical cytology samples prepared using ThinPrep and SurePath platforms: a review and meta-analysis

Abstract: ObjectiveTo compare unsatisfactory rates between the two major liquid-based cytology (LBC) platforms, namely ThinPrep (Hologic) and SurePath (Becton Dickinson).DesignThe authors performed both a systematic review and a meta-analysis. Inclusion criteria were English language, data presented on unsatisfactory rates for either ThinPrep or SurePath, utilising actual patient samples (ie, not laboratory manipulated samples) and no manipulation using acetic acid to increase the satisfactory rate. The authors searched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 53 publications
2
22
1
1
Order By: Relevance
“…In a meta-analysis of LBC for cervical cytology, the SurePath method had a significantly lower unsatisfactory sample rate than the ThinPrep method because of differences in cellular loss during the collection process. 20 In contrast, in the present study, LBC with the SurePath method had high accuracy and sensitivity.…”
Section: W E Demonstrated That Lbc Has High Diag-contrasting
confidence: 83%
“…In a meta-analysis of LBC for cervical cytology, the SurePath method had a significantly lower unsatisfactory sample rate than the ThinPrep method because of differences in cellular loss during the collection process. 20 In contrast, in the present study, LBC with the SurePath method had high accuracy and sensitivity.…”
Section: W E Demonstrated That Lbc Has High Diag-contrasting
confidence: 83%
“…Fontaine et al have shown that unsatisfactory rates are significantly lower when using SurePath instead of ThinPrep. 44 Although this was not shown in our previous study, 19 we then found similar results (an odds ratio of 0.74, 0.72 to 0.75) when comparing unsatisfactory rates between SurePath and ThinPrep.…”
Section: Explanation Of Main Resultssupporting
confidence: 67%
“…Slide preparation procedures from these media are different [1], [2]. Cells are normally collected using a Cervex-Brush (Rovers Medical Devices, Oss, Netherlands) but in PreservCyt cells are rinsed into the medium, dispersed by vortexing, and transferred to a microscope slide after vacuum filtration.…”
Section: Introductionmentioning
confidence: 99%